2010
DOI: 10.1523/jneurosci.1719-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Reward Prediction Error Coding in Dorsal Striatal Neurons

Abstract: In the current theory of learning, the reward prediction error (RPE), the difference between expected and received reward, is thought to be a key factor in reward-based learning, working as a teaching signal. The activity of dopamine neurons is known to code RPE, and the release of dopamine is known to modify the strength of synaptic connectivity in the target neurons. A fundamental interest in current neuroscience concerns the origin of RPE signals in the brain. Here, we show that a group of rat striatal neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
69
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(78 citation statements)
references
References 50 publications
7
69
2
Order By: Relevance
“…Singleneuron recording studies in monkeys have also implicated the changes in activity of a particular class of striatal neurons, termed tonically active neurons (TANs) and thought to be cholinergic interneurons, as a possible neuronal substrate of the prediction error signal (Joshua et al, 2008;Apicella et al, 2009). However, as in the study by Oyama et al (2010), these findings were reported in Pavlovian (i.e., classical) conditioning in which no behavioral response is required for reward, whereas no evidence of prediction error signaling has been observed during an instrumental task in which the rewarding outcome depends on an action (Morris et al, 2004). Thus, an intriguing question is whether the processing of prediction error signals by TANs occurs preferentially in specific learning situations.…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…Singleneuron recording studies in monkeys have also implicated the changes in activity of a particular class of striatal neurons, termed tonically active neurons (TANs) and thought to be cholinergic interneurons, as a possible neuronal substrate of the prediction error signal (Joshua et al, 2008;Apicella et al, 2009). However, as in the study by Oyama et al (2010), these findings were reported in Pavlovian (i.e., classical) conditioning in which no behavioral response is required for reward, whereas no evidence of prediction error signaling has been observed during an instrumental task in which the rewarding outcome depends on an action (Morris et al, 2004). Thus, an intriguing question is whether the processing of prediction error signals by TANs occurs preferentially in specific learning situations.…”
Section: Introductionmentioning
confidence: 58%
“…Functional brain imaging studies have identified prediction error-related activity in target structures of dopamine neurons, especially the striatum (Knutson et al, 2000;Pagnoni et al, 2002;McClure et al, 2003;O'Doherty et al, 2003O'Doherty et al, , 2004Schönberg et al, 2007). However, it remains unclear whether striatal neurons encode this type of prediction error (Schultz and Dickinson, 2000;Niv and Schoenbaum, 2008;Roesch et al, 2010), although it was recently reported that the activity of a group of striatal neurons in rats, presumed projection neurons, was linked to discrepancies between outcomes and their predictions, which suggests a coding of prediction error (Oyama et al, 2010). Singleneuron recording studies in monkeys have also implicated the changes in activity of a particular class of striatal neurons, termed tonically active neurons (TANs) and thought to be cholinergic interneurons, as a possible neuronal substrate of the prediction error signal (Joshua et al, 2008;Apicella et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In behavioral situations with contingencies changing about every 100 trials, dopamine neurons code the difference between current reward and reward history weighted by the last six to seven trials (Bayer et al, 2007). The occurrence of reward or reward prediction (positive prediction error) or their omission (negative prediction error) activates or depresses dopamine neurons in an inverse monotonic function of probability, such that the more unpredicted the event the stronger the response (de Lafuente and Romo, 2011;Enomoto et al, 2011;Fiorillo et al, 2003;Matsumoto and Hikosaka, 2009;Morris et al, 2006;Nakahara et al, 2004;Nomoto et al, 2010;Oyama et al, 2010;Satoh et al, 2003). Enomoto et al (2011) attempted to directly address whether the phasic dopamine response reflect the total future reward, as opposed to just the immediate reward.…”
Section: Phasic Dopamine Signals Represent Model-free Prediction Errorsmentioning
confidence: 99%
“…Using such a task, Schultz and colleagues have found that dopamine neurons code reward prediction error in their phasic response to the stimulus and the reward and that they also code reward uncertainty in their tonic activity between the CS and the outcome (Fiorillo et al 2003). We have recently recorded single-unit activity in the rat dorsal striatum and SNc during a probabilistic Pavlovian conditioning task and found that a group of neurons in the dorsal striatum codes reward prediction error information in the same manner as dopamine neurons in the SNc (Oyama et al 2010). Whereas in that study we focused on the neurons coding reward prediction error, in this study we analyzed the same data set looking for any task-related variation of activity.…”
mentioning
confidence: 95%